Numerical linear algebra with applications : using MATLAB - Ford, William (William H.) (Academic Press is an imprint of Elsevier, 2015)
Designed for those who want to gain a practical knowledge of modern computational techniques for the numerical solution of linear algebra problems, Numerical Linear Algebra with Applications contains all the material necessary for a first year graduate or advanced undergraduate course on numerical linear algebra with numerous applications to engineering and science. With a unified presentation of computation, basic algorithm analysis, and numerical methods to compute solutions, this book is ideal for solving real-world problems. It provides necessary mathematical background information for those who want to learn to solve linear algebra problems, and offers a thorough explanation of the issues and methods for practical computing, using MATLAB as the vehicle for computation. The proofs of required results are provided without leaving out critical details. The Preface suggests ways in which the book can be used with or without an intensive study of proofs. Six introductory chapters that thoroughly provide the required background for those who have not taken a course in applied or theoretical linear algebraDetailed explanations and examplesA through discussion of the algorithms necessary for the accurate computation of the solution to the most frequently occurring problems in numerical linear algebraExamples from engineering and science applications